PODCAST STORYTELLING: A NEW WAY OF TOURISM MARKETING IN INDONESIA - Peni Meliaty Hutabarat; Arius Krypton Onarelly; Rahmi Setiawati; Melisa Bunga Altamira (JCommsci - Journal of Media and Communication Science, 2023)
This study explores the trend of using podcasts and storytelling approaches as a new way to market regional tourism, in Indonesia. In the last two years, there has been a significant increase in access to audio on demand content in Indonesia. The use of new media such as podcasts in the promotion of the tourism sector is inevitable. Research on podcasts in Indonesia, especially tourism podcasts, is still not prevalent. However, the use of podcast platforms by actors in the tourism sector is starting to emerge. The storytelling approach is also increasingly important for the tourism sector because a good authentic story has the potential to create a better sense of place and connections. This study seeks to explore the opportunities and challenges of tourism podcasts, as well as the importance of the storytelling approach for marketing regional tourism in Indonesia. The method used in this study is a literature review which includes the process of reading and analyzing articles in journals, previous research reports, reference books and news related to podcasts. The results of the study show that podcast is an important marketing tool to enrich information on tourist destinations in Indonesia, and of course help encourage regional tourism marketing. This research is expected to be an input and recommendation to practitioners, government, communities, private sector and researchers to work together to equip tourism activities in various regions with podcasting and storytelling skills as a new way to develop tourism marketing in Indonesia.